PENYULUHAN DAMPAK PENGGUNAAN PESTISIDA DAN PENGENDALIAN KUALITAS PRODUK BAGI MASYARAKAT DESA PAMEKARAN, SUMEDANG, JAWA BARAT - Merita Bernik; Yeni Andriyani Setiawan (LP4MK STKIP PGRI Lubuklinggau, 2019)
The abundance of farmland in Pamekaran Village affects the many peoples who become farmers. In cultivating agricultural land and entering the time of harvest, the farmers of course try to keep the result of the harvest has a good quality one of them is by using pesticides. However, the use of pesticides among farmers has not been all done with the correct procedures that can have a major impact on health and the environment. Therefore it is necessary to counsel so that farmers can know and understand about the impact of pesticides and product quality control so that the harvested yield will have the best quality and can also minimize environmental damage.